Standing united or falling divided? High stakes bargaining in a TV game show - van Dolder, Dennie; van den Assem, Martijn J.; Camerer, Colin F.; Thaler, Richard H. (American Economic Association, 2015)
We examine high stakes three-person bargaining in a game show where contestants bargain over a large money amount that is split into three unequal shares. We find that individual behavior and outcomes are strongly influenced by equity concerns: those who contributed more to the jackpot claim larger shares, are less likely to make concessions, and take home larger amounts. Contestants who announce that they will not back down do well relative to others, but they do not secure larger absolute amounts and they harm others. There is no evidence of a first-mover advantage and little evidence that demographic characteristics matter.